2019
DOI: 10.4103/ijpvm.ijpvm_25_19
|View full text |Cite
|
Sign up to set email alerts
|

Advanced parental age and risk of positive autism spectrum disorders screening

Abstract: Background: Autism Spectrum Disorder (ASD) is a life -long neurodevelopmental disorder and significantly influences the quality of life in children. The screening of ASD in children aged between 16-30 months to early detection and early intervention for better prognosis. Methods: This cross-sectional study was conducted in the southwest of Iran (Yasuj) with dominant Lore ethnicity in 2017. A total of 1504 mother- child pairs with children aged between 16-30 months were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…In contrast to our study, many studies confirmed the strong correlation between the increased risk of having ASD in the children and the age of the parent [24,38] or the age of mothers [50] or the increase in the order of the childbirth.…”
Section: Regarding the Age Of Parentscontrasting
confidence: 99%
“…In contrast to our study, many studies confirmed the strong correlation between the increased risk of having ASD in the children and the age of the parent [24,38] or the age of mothers [50] or the increase in the order of the childbirth.…”
Section: Regarding the Age Of Parentscontrasting
confidence: 99%
“… Ben Itzchak et al (2011) , Durkin et al (2008) , Hultman et al (2011) , King et al (2009) , Lampi et al (2013) , Lung et al (2018) , Manzouri et al (2019) , Merikangas et al (2017) , Reichenberg et al (2006) , Rieske and Matson (2020) , Shelton and Tancredi (2010) , Shimada et al (2012) , Taylor et al (2019) , Tsuchiya et al (2008) , and Van Balkom et al (2012) …”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of ASD in several Asian and American countries is the United States (90 per 10 000), South Asia (1 in 93), Japan (13 per 10 000), and China (9,8 per 10 000). (25)…”
Section: Research Developments Per Yearmentioning
confidence: 99%